Gulf security and the U.S. military regime survival and the politics of basing - Gresh, Geoffrey F. (Stanford University Press, 2015)
The U.S. military maintains a significant presence across the Arabian Peninsula but it must now confront a new and emerging dynamic as most Gulf Cooperation Council countries have begun to diversify their political, economic, and security partnerships with countries other than the United States--with many turning to ascending powers such as China, Russia, and India. The analysis of the cases offers a fresh perspective on how the United States has adapted to sometimes rapidly shifting Middle East security dynamics and factors that influence a host nation's preference for eviction or renegotiation, based on its perception of internal versus external threats.